Exposure to neonicotinoids and serum testosterone in men, women, and children. Issue 6 (22nd February 2022) - Mendy, Angelico; Pinney, Susan M.
Abstract: Neonicotinoids are the most used pesticides in the world and, despite being harmful to honeybees, they are considered safe for mammals. However, they have been associated with decreasing testosterone levels in several experimental animal models. In the present study, we aimed to determine the association of urinary neonicotinoids with serum testosterone in humans. We analyzed data on 2014 male and female participants to the National Health and Nutrition Examination Survey conducted between 2015 and 2016 aged 6 or older. In linear regression adjusted for age and potential confounders, serum total testosterone was 37.78% lower with 10‐fold increase in urinary total neonicotinoids (95% CI: −58.82, −6.00), 20.81% lower with 10‐fold increase in urinary 5‐hydroxy‐imidacloprid (95% CI: −34.94, −3.62) and 25.01% lower with 10‐fold increase in urinary n ‐desmethyl‐acetamiprid (95% CI: −39.80, −6.58) among males. Serum free androgen index (FAI) was also decreased with higher urinary n ‐desmethyl‐acetamiprid. In females, serum total testosterone was 32.91% lower with 10‐fold increase in urinary total neonicotinoids (95% CI: −54.93, −0.13), 21.32% lower with 10‐fold increase in urinary 5‐hydroxy‐imidacloprid (95% CI: −29.31, −12.42) and 15.42% lower with urinary detection of 5‐hydroxy‐imidacloprid (95% CI: −22.80, −7.34). FAI was likewise reduced with higher urinary levels of 5‐hydroxy‐imidacloprid and N ‐desmethyl‐acetamiprid. In conclusion, this study using a sample representative of the US population is the first to report that exposure to neonicotinoids is associated with decreased serum testosterone levels in humans. However, future prospective studies are warranted to confirm these findings.